Narrative Identity: What Is It? What Does It Do? How Do You Measure It?. (March 2018) - McAdams, Dan P.
In this commentary, I provide an historical perspective on the methodological and conceptual issues that are raised by the papers in this volume, with a focus on the idea of narrative identity as it relates to autobiographical memory. Referring back to the emergence of the concept of narrative identity in the 1980s, I consider old and new ideas regarding the form and function of narrative identity and methodological challenges that arise in efforts to measure and code psychologically important features of life-narrative accounts.